Sustainable dyeing of cotton, silk and leather using natural dye from Bixa orellana seeds: extraction, optimization and assessment of antibacterial activity - Muruganandham, Moorthy; Tamilselvi, Yuvaraj; Sivasubramanian, Kanagasabapathy; Velmurugan, Palanivel; Oleyan Al-Otibi, Fatimah; Sivakumar, Subpiramaniyam (Frontiers in Chemistry, 2025)
IntroductionNatural dyes offer an eco-friendly alternative to synthetic colorants in textile processing. This study explores the sustainable dyeing of cotton, silk, and leather using pigment-rich extracts from Bixa orellana seeds, with a focus on process optimization and antibacterial efficacy.Materials and methodsUsing an array of extraction solvents [water, methanol, ethanol, ethanol: methanol (1:1)] and extraction techniques [direct heat (DH), ultrasonic water bath (USB), ultrasonic probe, (USP)], Bixa orellana seeds were utilized to produce a yellow-orange dye. The color strength of the extracted dye was investigated using a UV-Visible spectrophotometer to measure the absorbance wavelength. The functional groups identified in the extracted natural dye were described using an FTIR spectrophotometer.Results and discussionUsing methanol as the solvent and 5 g of seed at 60°C for 60 min, the highest color yield was observed in USB. Using the ultrasonic water bath dyeing method at 60°C for 40 min without using any moderant, cotton, silk fabric, and leather were effectively colored in a yellow-orange color. The L*, a*, and b* values of the dyed material treated using the USB approach were 80.95, 4.52, 75.35 for cotton, 88.65, -1.35, 62.85 for silk, and 79.55, 015.35, 66.45 for leather, respectively. Compared to the other bacterial reduction, 85.25% of the colored materials showed substantial antibacterial action against Staphylococcus sp. Vibrio sp. (76.69%), Pseudomonas sp. (75.83%), Klebsiella sp. (74.24%), and Micrococcus sp. (74.21%) were the following most prevalent bacteria. The ultraviolet protection factor (UPF) measurements showed that leather and cotton treated with B. orellana seed dye had higher UV radiation shielding properties.